"Place" and "Non‐Place": A Model for the Strategic Design of Place‐Centered Services. (27th February 2013) - Gasté, Yann; Gentes, Annie; Pain, Frédérique; Lively, Scott
Abstract This paper describes the "Periscope, " a probe tested in the Paris underground to better understand users' relation to space in mobility. Our research found that testers qualify their relation to the Metro in a way that is both depersonalized and efficient, as well as deeply personal and social. We also found that mobility is experienced not only as controlled circulation but also as a meaningful "journey" that can be articulated and shared. To account for this dual perception of physical space and motion, we propose to use the anthropological concepts of "non‐place" and "place." This theoretical framework offers useful guidelines for the design of what we propose to call "place‐centered services" that, first combine the dynamic synchronization of the journey and users' dual relation to spaces, and second categorize the actors that contribute to the information system and services. © 2013 Alcatel‐Lucent.